Studi Pengembangan Konstruksi Rumah Kayu Sistem Bongkar Pasang Berdasarkan Konsep Struktur Kayu Tradisional Sumatera Selatan The Study of Knock Down Timber Construction House Based on the Concept of South Sumatra Timber House Structure - Ari Siswanto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2004)
This research is based on the existence of South Sumatra traditional timber structure which is characterized by knock down houses and spread out in many regions in the form of traditional houses. The local knowledge in the form of timber house is ancestors inheritage which proves to be adaptive to environment and local culture. Knock-down timber house is home industry of the people who live in Tanjung Batu which is widely known and marketed but still has some technical weaknesses.This research focuses on designing knock-down timber house which is based on the concept of interlocking techniques, without nails, using timber with 4 meters long and planning a manual for setting up timber house. The implementation of the research is constructing a timber house with 1: 2 scales. Detail and timber join of 1 : 2 scales is very difficult because timber dimension is too small. However, knock down implementation can be done in a good manner.Knock-down timber house with interlocking techniques can be set up without nails and uses timber efficiently and set up it systematically by manual as a guidance. Consumers of knock-down timber house are expected to be able to erect the house by themselves, so it reduces the erection cost